Studying In Australia To Improve English Speaking Competence: Revisited - Munir Ahmad (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
This study investigates Indonesian postgraduate studentsÃ¢â¬â¢ perceptions about their improvement in English speaking competence during their period of study in Australia. Statistical tests show that the students who had spent more than one year in Australia perceived their English speaking competence as higher than those who had stayed for less than a year. However, the respondents expressed uncertainty as to whether their English would improve, even if they were to extend their stay in this English speaking country because of their Indonesian circles. They believed that they have improved their confidence in speaking English because of their stay in Australia. Finally, learning from this study some suggestions for the students learning English in Indonesia are proposed.